Ellipsis in abstracts of business journal articles in english and vietnamese - Nguyễn Thị Thanh Nga (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
There is no doubt that natural phenomena hold a significant key in human life. Therefore, choosing a suitable way to identify and describe natural phenomena is indispensable in the process of communication. How to use language to describe them effectively is one of the main purposes of the researcher. This thesis is aimed at investigating the syntactic and semantic features of words and expressions describing “rain, wind, wave, sunshine and cloud” in English and Vietnamese. Basing on the data collected from different sources, the thesis provides a presentation of the syntactic and semantic features of words and expressions describing “rain, wind, wave, sunshine and cloud” in English and Vietnamese. Another aim of the thesis which the author desires to reach is to point out the similarities and differences in the syntactic and semantic features in the two languages. Through the study, the author hopes to help the learners and the readers to make sense of language usage, world view as well as culture between the two peoples.